Popular participation in rural development : the New Zealand/Solomon Islands customary land reforestation project on Malaita : a thesis submitted in partial fulfilment of the requirements of the degree of Master of Philosophy, Department of Sociology, Massey University - Clark, Kevin; Clark, Kevin (Massey University, 1991)
This study explores the concept of popular participation in rural development with particular reference to the forestry sector and its role in poverty alleviation. It starts with the premise that popular participation is necessary to address poverty issues and that popular participation can be promoted through aid projects funded by bilateral aid donors and implemented through government bureaucracies. The case study of an aid-funded social forestry project in Solomon Islands highlights impediments to aid agency promotion of popular participation: different objectives from local people, a blueprint approach to project management, and lack of experience in community development, and identifies some of the difficulties of working with Third World bureaucracies: a top down approach to development, limited resources, inexperience, and a weak infrastructure. Nevertheless, it concludes that a participatory approach to project planning and implementation is possible.
Keywords: Rural development; Community participation; International aid; Forestry; Project planning